Curling in Canada: From Gathering Place to International Spectacle - Mair, Heather (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2007)
Curling is a central part of winter life for many Canadians and our curlers dominate the world stage. Yet the topic remains dramatically understudied. Building on the limited writing in this area and presenting research undertaken in curling clubs across western Canada, the author seeks to help fill this gap by exploring the changing role of curling in the construction of social identities at the local community and national level. It is argued that while curling plays an undeniable, if muted, role in the construction of Canada's image, this identity is being increasingly subjected to a number of internal and external pressures that have the potential to lead to great change.